A bilevel approach to enhance prefixed traffic signal optimization. (September 2019) - García-Ródenas, Ricardo; López-García, María L.; Sánchez-Rico, María Teresa; López-Gómez, Julio Alberto
Abstract: The segmentation of multivariate temporal series has been studied in a wide range of applications. This study investigates a challenging segmentation problem on traffic engineering, namely, identification of time-of-day breakpoints for pre-fixed traffic signal timing plans. A large number of urban centres have traffic control strategies based on time-of-day intervals. We propose a bilevel optimization model to address simultaneously the segmentation problems and the traffic control problems over these time intervals. Efficient memetic algorithms have been developed for the bilevel model based on the hybridization of the particle swarm optimization, genetic algorithms or simulated annealing with the Nelder–Mead method. Numerically the effectiveness of the algorithms using real and synthetic data sets is demonstrated. We address the problem of automatically estimating the number of time-of-day segments that can be reliably discovered. We adapt the Bayesian Information Criterion, the PETE algorithm and a novel oriented-problem approach. The experiments show that this last method gives interpretable results about the number of reliably necessary segments from the traffic-engineering perspective. The experimental results show that the proposed methodology provides an automatic method to determine the time-of-day segments and timing plans simultaneously. Graphical abstract: Highlights: A bilevel model for simultaneously determining TODs and traffic signal optimization. Memetic algorithms based on PSO, SA, GA and Nelder Mead are proposed for bilevel model. A set of computational tests on synthetic and real data sets. A novel oriented-problem approach to determine optimal number of TODs.